Model Arsitektur ERP Berbasis TOGAF ADM untuk Pengendalian Internal Sub-Ledger pada Sistem Informasi Akuntansi Manufaktur - Indah; Rudianto; Amrin; Untung Rohwadi (JUSTIKA : Jurnal Sistem Informasi Akuntansi, 2026)
This study designs an Enterprise Resource Planning (ERP) architecture model based on the TOGAF Architecture Development Method (ADM) to strengthen internal control in Accounting Information Systems (AIS) for manufacturing. The research addresses the classical problem of data discrepancy between operational transactions and the General Ledger (GL) by introducing a multi‑tier maker‑checker mechanism. Data collection was conducted through participatory observation, in‑depth interviews, document analysis, and requirement elicitation, which were transformed into user stories and constraint rules. The proposed model enforces rigid parameters such as Direct Posting = FALSE on Chart of Accounts and Cleared = FALSE/TRUE on cash sub‑ledger entries. Validation was performed using extreme transaction scenario simulations, including manual voucher corrections, premature receivable clearance, and vendor billing without physical verification. Results show that the model successfully rejects these failure cases, ensuring audit trail integrity and compliance with segregation of duties. The novelty of this research lies in embedding internal control constraints directly into ERP technical parameters, bridging the gap between automation convenience and governance requirements. This blueprint contributes to both academic discourse and practical ERP implementation, while future studies are recommended to conduct pilot testing in real manufacturing environments and integrate AI‑driven anomaly detection for real‑time audit enhancement.